Auto-Allo Graft Parallel Juxtaposition for Improved Neuroregeneration in Peripheral Nerve Reconstruction Based on Acellular Nerve Allografts. Issue 3 (September 2019) - Boriani, Filippo; Savarino, Lucia; Fazio, Nicola; Pedrini, Francesca Alice; Fini, Milena; Nicoli Aldini, Nicolò; Martini, Lucia; Zini, Nicoletta; Bernardini, Marco; Bolognesi, Federico; Marchetti, Claudio; Baldini, Nicola
Abstract : Introduction: Nerve repair poses a significant surgical challenge, and much research on this topic for improvement in reconstruction of segmental defects is ongoing. The aims of the study were to reconfirm the accuracy and safety of a previously described nerve decellularization method on a larger experimental population of rabbits, as well as on human nerves, and to establish in vivo the efficacy of a new-concept mixed graft, comprising autologous and acellular nerve allograft components within the same graft. Methods: Acellular nerve allografts were implanted into tibial nerve defects of 5 rabbits (group A), autografts were implanted, representing the criterion standard, in other 5 animals (group B), and the innovative technique was used in the remaining 5 (group C). Twelve weeks postoperatively, nerve conduction evaluations were performed; animals were euthanatized, and grafts were harvested and morphologically, histomorphometrically, and immunohistochemically analyzed. Eventually, a preliminary in vitro validation of the decellularization method was performed on human nerves from a cadaver. Results: No clinical adverse effect was revealed during all the experimental times. No tissue reaction was observed, and in all groups, regenerated fascicles and bundles were shown by histology. However, both histology and histomorphometry demonstrated a better regenerative efficiency in group C. The morphological evaluation of the human nerve treated with the novel method showed complete decellularization. Conclusion: The microsurgical combined model demonstrated a better neuroregeneration than did pure autografts and acellular nerve allografts. The decellularization method seemed effective also on human nerves. Deeper investigations are necessary to further validate and transfer this new encouraging protocol to the clinical arena.